Ignorance or culture war? Christian nationalism and scientific illiteracy. (November 2021) - Perry, Samuel L.; Baker, Joseph O.; Grubbs, Joshua B.
Religiously conservative Americans consistently demonstrate lower scientific literacy than other Americans. Some argue, however, that Americans' scientific literacy is contingent on subcultural conflict, showing differences in scientific literacy that emerge only on religiously contested scientific claims. Building on these insights, we find that the most salient factor explaining Americans' divergence on contested (though not on uncontested) scientific claims is not religious commitment or conservatism per se, but an ideology that seeks political—and consequently epistemic—dominance: Christian nationalism. National data show that Christian nationalism is unassociated with Americans' answers on questions about uncontested scientific knowledge. However, Christian nationalism is the strongest predictor of incorrect answers on questions about religiously contested scientific claims. Contemporary "culture war" debates over science have little to do with outright ignorance of science, nor are they strictly about religiosity or theological conservatism. Rather, disputes over science and religion reflect politically motivated denials of scientific facts that threaten Christian nationalism's claims to epistemic and cultural authority.